2014
DOI: 10.1097/pai.0b013e3182a8da2e
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Pattern in Enchondroma and Chondrosarcoma

Abstract: The results point to the use of the vascular pattern classification as a prognostic tool in CSs and to differentiate low-grade from moderate-grade/high-grade CSs. Vascular pattern might be also used to complement histologic grade, VEGF immunostaining, and microvascular density, for indicating a patient's prognosis. Low-grade CSs develop under low neoangiogenesis, which conforms to the slow growth rate of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Without neovascularization the size of a tumor is inherently limited to 1–5 mm due to restricted oxygen and nutrient availability [ 65 ]. Although conventional chondrosarcomas remain poorly vascularized compared to other tumors [ 66 , 67 ], which may contribute to the cartilage like differentiation and systemic chemotherapy resistance, induction of angiogenesis is the major limiting step towards local invasion and metastasis. This is reflected by a low rate of vascularization in G1 conventional chondrosarcomas, which is largely enhanced in the significantly more aggressive G2 and G3 chondrosarcomas [ 66 , 68 ].…”
Section: Hypoxia and Angiogenesis In The Bone Nichementioning
confidence: 99%
See 2 more Smart Citations
“…Without neovascularization the size of a tumor is inherently limited to 1–5 mm due to restricted oxygen and nutrient availability [ 65 ]. Although conventional chondrosarcomas remain poorly vascularized compared to other tumors [ 66 , 67 ], which may contribute to the cartilage like differentiation and systemic chemotherapy resistance, induction of angiogenesis is the major limiting step towards local invasion and metastasis. This is reflected by a low rate of vascularization in G1 conventional chondrosarcomas, which is largely enhanced in the significantly more aggressive G2 and G3 chondrosarcomas [ 66 , 68 ].…”
Section: Hypoxia and Angiogenesis In The Bone Nichementioning
confidence: 99%
“…Although conventional chondrosarcomas remain poorly vascularized compared to other tumors [ 66 , 67 ], which may contribute to the cartilage like differentiation and systemic chemotherapy resistance, induction of angiogenesis is the major limiting step towards local invasion and metastasis. This is reflected by a low rate of vascularization in G1 conventional chondrosarcomas, which is largely enhanced in the significantly more aggressive G2 and G3 chondrosarcomas [ 66 , 68 ]. VEGF and FGF2, which have an intense crosstalk, are the two main growth factors involved in chondrosarcoma angiogenesis [ 65 ].…”
Section: Hypoxia and Angiogenesis In The Bone Nichementioning
confidence: 99%
See 1 more Smart Citation
“…However, different studies have evaluated the role of miRNAs in angiogenesis and metastatic progression in CS. Angiogenesis is associated with worse prognosis in CS [122]. It has been shown that CCL5 induces downregulation of miR-199a and miR-200b, not being able to regulate VEGF-A, resulting in higher VEGF-A levels in cells [123,124].…”
Section: Exosomes In Csmentioning
confidence: 99%
“…CS is classified into three grades along the malignancy. Angiogenesis has been seen in tumor tissue to be associated with the upgrading of malignancy [116]. There are several reports about the regulation of VEGF and angiogenesis through the control of miRNAs in CS.…”
Section: The Functions Of Mirna and Exosomes In Sarcomamentioning
confidence: 99%